Analysis of Protein Separation Mechanism in Charged Ultrafiltration Membrane - Danu Ariono; Putu Teta P. Aryanti; Anita Kusuma Wardani; I Gede Wenten (Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
The separation mechanism of proteins on a charged ultrafiltration membrane was analyzed using the extended Nernst